Enhancing early childhood’s fine motor development through educational games - Hasanah, Qoriatul; Aziz, Thorik (Journal of Early Childhood Care and Education, 2024)
This study investigates the effectiveness of educational game tools in developing fine motor skills among early childhood students at Kemala Bhayangkari 80 Sampang Kindergarten. Using a descriptive qualitative approach, it involved 15 children (ages 4-6), five teachers, and three parents over a six-month period through observations, interviews, and document analysis. Findings show that tools like plasticine, building blocks, puzzles, finger painting, picture books, and beading each uniquely support fine motor skills such as finger strength, coordination, and creative control. An average improvement of 40-45 points per tool type was observed. This study highlights the importance of a structured educational game-based curriculum, ongoing teacher training, and school-family collaboration to maximize tool efficacy. Future research is recommended to explore the long-term impact of educational game tools on children’s academic performance and to assess the potential of technology-enhanced tools for fine motor skill development.